LRP1 regulates peroxisome biogenesis and cholesterol homeostasis in oligodendrocytes and is required for proper CNS myelin development and repair - Lin, Jing-Ping; Mironova, Yevgeniya A; Shrager, Peter; Giger, Roman J (eLife, 2017)
Low-density lipoprotein receptor-related protein-1 (LRP1) is a large endocytic and signaling molecule broadly expressed by neurons and glia. In adult mice, global inducible (Lrp1flox/flox;CAG-CreER) or oligodendrocyte (OL)-lineage specific ablation (Lrp1flox/flox;Pdgfra-CreER) of Lrp1 attenuates repair of damaged white matter. In oligodendrocyte progenitor cells (OPCs), Lrp1 is required for cholesterol homeostasis and differentiation into mature OLs. Lrp1-deficient OPC/OLs show a strong increase in the sterol-regulatory element-binding protein-2 yet are unable to maintain normal cholesterol levels, suggesting more global metabolic deficits. Mechanistic studies revealed a decrease in peroxisomal biogenesis factor-2 and fewer peroxisomes in OL processes. Treatment of Lrp1−/− OPCs with cholesterol or activation of peroxisome proliferator-activated receptor-γ with pioglitazone alone is not sufficient to promote differentiation; however, when combined, cholesterol and pioglitazone enhance OPC differentiation into mature OLs. Collectively, our studies reveal a novel role for Lrp1 in peroxisome biogenesis, lipid homeostasis, and OPC differentiation during white matter development and repair.
Keywords: CNS Myelin Repair; Oligodendrocyte differentiation; Peroxisome Biogenesis; Cholesterol Homeostasis; LRP1; mouse